Copper-free medium-entropy alloy interlayer, application of copper-free medium-entropy alloy interlayer and welding method of titanium alloy and stainless steel
By using copper-free medium-entropy alloy interlayer, the problem of relying on copper-based filler materials for welding between titanium alloy and stainless steel is solved, and high-strength metallurgy combination and corrosion resistance are improved.
Patent Information
- Application Number
- CN202510187000.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-29
AI Technical Summary
The existing welding technology of titanium alloys and stainless steel relies on copper-based filler materials, resulting in weak welded joints in corrosion-resistant environments, affecting structural safety and service life.
A copper-free intermediate entropy alloy interlayer is used, consisting of Co, Ni and V, with a mass percentage of Co: 34% to 40%, Ni: 34% to 40%, V: 20% to 32%, which is used for laser welding of titanium alloy and stainless steel to form a high-strength metallurgical bond.
The high-strength metallurgy combination of titanium alloy and stainless steel is achieved, structural failure caused by copper element enrichment is avoided, and the tensile strength and corrosion resistance of welded joints are improved.
Smart Images

Figure CN119897629A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of laser welding technology, and in particular to a copper-free medium-entropy alloy interlayer and its application, and a welding method for titanium alloy and stainless steel. Background Art
[0002] The titanium / steel composite structure can not only give full play to the advantages of titanium alloy such as high specific strength and good corrosion resistance, but also take into account the excellent cost-effectiveness of steel. It has important applications in aerospace, electronic chemical industry, nuclear energy and other fields. Considering the economy, feasibility and convenience of actual processing, laser welding has high processing accuracy and highly free operability, and is the preferred method for welding titanium / steel structures. It is difficult to connect titanium / steel dissimilar metals. Due to the differences in their physical and metallurgical properties, hard and brittle intermetallic compounds will be produced at the interface after welding, which will cause the joint to crack and fail under the action of residual thermal stress.
[0003] At present, titanium / steel welding mainly uses pure copper or copper-based filler materials, but due to the poor corrosion resistance of copper, for components used in nuclear power and marine environments, copper-rich welded joints will become the weak point of the overall structure. Therefore, achieving copper-free titanium / steel welding is of great significance to improving structural safety and service life. Summary of the invention
[0004] To this end, the technical problem solved by the present application is to provide a copper-free medium-entropy alloy interlayer and its application, and a welding method for titanium alloy and stainless steel, which can effectively solve the problem of existing fusion welding of titanium alloy / stainless steel on the dependence on copper-based filler materials.
[0005] In view of this, the present application provides a copper-free medium-entropy alloy interlayer composed of Co, Ni and V, which, in terms of mass percentage, include: Co: 34% to 40%, Ni: 34% to 40%, and V: 20% to 32%.
[0006] In some embodiments, the copper-free medium-entropy alloy interlayer includes: Co: 34.96% to 39.31%, Ni: 34.82% to 38.75%, and V: 22.94% to 30.22%.
[0007] In some embodiments, the method for preparing the copper-free medium-entropy alloy interlayer comprises the following steps:
[0008] A) preparing ingredients according to the mass percentage of the copper-free medium-entropy alloy interlayer, and then smelting to obtain an alloy ingot;
[0009] B) preparing the alloy ingot into copper-free medium-entropy alloy interlayers in different usage forms.
[0010] In some embodiments, the copper-free medium-entropy alloy interlayer is used in one or more of the following shapes: molten alloy block, molten alloy crushed particles, molten alloy flakes, molten alloy powder, quenched foil strip and powder sintered body.
[0011] The present application also provides the use of the copper-free medium-entropy alloy interlayer in the laser welding connection of titanium alloy and stainless steel.
[0012] The present application also provides a method for welding titanium alloy and stainless steel, comprising the following steps:
[0013] S1) pretreating the surfaces of the titanium alloy and the stainless steel;
[0014] S2) placing a copper-free medium entropy alloy intermediate layer at a position to be welded between the titanium alloy and the stainless steel obtained in step S1) to obtain an assembly component;
[0015] S3) performing laser welding on the assembly components;
[0016] The copper-free medium-entropy alloy intermediate layer is made of the copper-free medium-entropy alloy interlayer according to any one of claims 1 to 4.
[0017] In some embodiments, the thickness of the copper-free medium entropy alloy intermediate layer in the assembly component ranges from 0.5 mm to 1.5 mm.
[0018] In some embodiments, the titanium alloy is an alpha titanium alloy, a near-alpha titanium alloy, an alpha-beta titanium alloy, a beta titanium alloy or a commercially pure titanium alloy, and the stainless steel is an austenitic stainless steel, a ferritic stainless steel, a martensitic stainless steel, a duplex stainless steel or a precipitation hardening stainless steel.
[0019] In some embodiments, the laser power of the laser welding is 900-1100 W, the speed is 15 mm / s-20 mm / s, and the laser defocus is -25 mm--15 mm.
[0020] In some embodiments, during laser welding, the laser spot is offset by 0.1 mm to 0.3 mm toward the stainless steel after being aligned with the middle of the copper-free medium entropy alloy intermediate layer.
[0021] The present application provides a copper-free medium entropy alloy interlayer, which includes, by mass percentage, Co: 34% to 40%, Ni: 34% to 40%, and V: 20% to 32%. The copper-free medium entropy alloy interlayer made of the copper-free medium entropy alloy interlayer of the present application is suitable for melting and welding titanium alloy and stainless steel, so that the joint performance can meet the use requirements of various application conditions. Compared with other commercial intermediate layers, the copper-free medium entropy alloy intermediate layer used in the present application does not contain the Cu element, which fundamentally avoids the structural failure caused by the enrichment of the Cu element. The structure of the copper-free medium entropy alloy intermediate layer is a face-centered cubic structure, and the solid solubility between Co, Ni and Fe is strong, and the solid solubility of V with Fe at high temperature is also high. After welding, the main body of the titanium alloy / stainless steel joint is still a face-centered cubic structure, which can effectively relieve the residual stress after welding. In addition, due to the high solid solution of V and Ti, the performance of the compound at the interface is significantly improved, thereby achieving a high-strength metallurgical bonding of titanium alloy and stainless steel.
[0022] Furthermore, due to the presence of Co, Ni and Fe elements in stainless steel, the main body of the weld presents a single-phase FCC structure after welding and has good plasticity, while a Ti-rich layer and a compound layer are generated on the titanium alloy side. Since the V element has a high solid solubility in Ti, the performance of the compound in the reaction layer can be greatly improved, the brittleness of the joint can be alleviated, and the weld strength can be effectively improved. The tensile strength of the resulting titanium alloy / stainless steel joint can reach 235MPa~331MPa, which is higher than the strength of other high-entropy alloy intermediate layer fusion welding and is equivalent to the strength of the pure copper intermediate layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an electron microscope photograph of the copper-free medium-entropy alloy intermediate layer prepared in Example 1.
[0024] Figure 2 This is an electron microscope photograph of the cross section of a laser welded joint obtained by using the copper-free medium-entropy alloy intermediate layer prepared in Example 1 for TC4 titanium alloy and 316L stainless steel.
[0025] Figure 3 This is an electron microscope photograph of the microstructure of one side of TC4 after welding in Example 1. DETAILED DESCRIPTION
[0026] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0027] The disclosure below provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the disclosure of the present application, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the various specific processes and material examples provided by the present application, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.
[0028] At present, high entropy alloy is a new type of alloy composed of four or more principal elements. Compared with traditional alloys, it has the characteristics of high strength and toughness, hysteresis diffusion, etc. Its appearance provides a new idea for solving the problem of titanium / steel dissimilar metal connection, that is, high entropy of welds. High entropy welds have the characteristics of high entropy alloys. The high entropy effect can form a multi-principal element solid solution structure at the titanium / steel interface, inhibiting the formation of hard and brittle intermetallic compounds; based on the cocktail effect, the thermal expansion coefficient of high entropy alloys can be flexibly controlled by adjusting the composition, so that it is between titanium and steel, forming a reasonable buffer layer, and reducing the interface stress caused by the mismatch of thermal expansion coefficients between titanium and steel.
[0029] Taking into account the dilution effect of the base material on the weld, a medium-entropy alloy (an alloy composed of three main elements) is selected as an effective means to achieve high entropy of the weld, which can not only achieve a reliable connection of titanium / steel, but also solve the problem of dependence on copper-based filler materials during titanium / steel fusion welding.
[0030] Specifically, the present application provides a copper-free medium-entropy alloy interlayer, which relates to the field of laser welding technology, specifically to the field of nuclear power, and is composed of three main elements: Co, Ni and V, in terms of mass percentage, including: Co: 34% to 40%, Ni: 34% to 40%, V: 20% to 32%.
[0031] In the copper-free medium entropy alloy interlayer of the present application, the Co element can refine the grains, improve the room temperature strength and plasticity of the titanium alloy / stainless steel joint, and improve the high temperature oxidation performance. The content of Co is 34% to 40%, specifically, the content of Co is 34.96% to 39.31%, and more specifically, the content of Co is 34%, 34.5%, 34.96%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38.5%, 39%, 39.31%, 39.5% or 40%.
[0032] The Ni element promotes dynamic recrystallization and improves the hot working plasticity of the titanium alloy / stainless steel joint. The Ni content is 34% to 40%, specifically, the Ni content is 34.82% to 38.75%, and more specifically, the Ni content is 34%, 34.5%, 34.82%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38.5%, 38.75%, 39%, 39.5% or 40%.
[0033] The V element can refine the grains and improve the strength and toughness of titanium alloy / stainless steel. The V content is 20% to 32%, specifically, the V content is 22.94% to 30.22%, more specifically, the V content is 20%, 21%, 22%, 22.94%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 30.22%, 31% or 32%.
[0034] The copper-free medium-entropy alloy interlayer made of the copper-free medium-entropy alloy interlayer of the present application is suitable for melt welding of titanium alloy and stainless steel, so that the joint performance can meet the use requirements of various application conditions. Compared with other commercial intermediate layers, the copper-free medium-entropy alloy intermediate layer used in the present application does not contain the Cu element, which fundamentally avoids the structural failure caused by the enrichment of the Cu element. The structure of the copper-free medium-entropy alloy intermediate layer is a face-centered cubic structure, and the solid solubility between Co, Ni and Fe is strong, and the solid solubility of V in Fe at high temperature is also high. After welding, the main body of the titanium alloy / stainless steel joint is still a face-centered cubic structure, which can effectively relieve the residual stress after welding. In addition, due to the high solid solution of V and Ti, the performance of the compound at the interface is significantly improved, thereby achieving a high-strength metallurgical bond between titanium alloy and stainless steel.
[0035] Furthermore, due to the presence of Co, Ni and Fe elements in stainless steel, the main body of the weld presents a single-phase FCC structure after welding and has good plasticity, while a Ti-rich layer and a compound layer are generated on the titanium alloy side. Since the V element has a high solid solubility in Ti, the performance of the compound in the reaction layer can be greatly improved, the brittleness of the joint can be alleviated, and the weld strength can be effectively improved. The tensile strength of the resulting titanium alloy / stainless steel joint can reach 235MPa~331MPa, which is higher than the strength of other high-entropy alloy intermediate layer fusion welding and is equivalent to the strength of the pure copper intermediate layer.
[0036] The method for preparing the copper-free medium-entropy alloy interlayer comprises the following steps:
[0037] A) preparing ingredients according to the mass percentage of the copper-free medium-entropy alloy interlayer, and then smelting to obtain an alloy ingot;
[0038] B) preparing the alloy ingot into copper-free medium-entropy alloy interlayers in different usage forms.
[0039] In the above preparation method, the raw materials used in the batching can be selected according to the raw materials well known to those skilled in the art, and this application does not impose any special restrictions on this. The smelting can be carried out by a smelting method well known to those skilled in the art, for example, the smelting can be carried out by arc melting.
[0040] After smelting, an alloy ingot is obtained. According to the different shapes of the interlayer required for laser welding, the above alloy ingot can be further prepared into medium-entropy alloy interlayers in different usage forms; specifically, the shapes of medium-entropy alloy interlayers in different usage forms include one or more of smelting alloy blocks, smelting alloy particles, smelting alloy flakes, smelting alloy powders, rapidly cooled foil strips and powder sintered bodies, among which the smelting alloy blocks, smelting and gold particles, smelting alloy flakes and smelting alloy powders are all obtained by simply processing the above alloy ingots to obtain interlayers in different forms, the rapidly cooled foil strip is an alloy ingot that is subjected to rapid cooling and other treatments to obtain a foil strip-shaped interlayer, and the powder sintered body is a sintered body interlayer obtained by atomizing, sintering and other treatments on the alloy ingot. The specific method of obtaining the above interlayers of different shapes can be carried out in a manner familiar to those skilled in the art, and the present application does not impose any special restrictions on this.
[0041] The present application also provides the use of the above copper-free medium-entropy alloy interlayer in laser welding of titanium alloy and stainless steel.
[0042] The present application also provides a method for welding titanium alloy and stainless steel, comprising the following steps:
[0043] S1) pretreating the surfaces of the titanium alloy and the stainless steel;
[0044] S2) placing a copper-free medium entropy alloy intermediate layer at a position to be welded between the titanium alloy and the stainless steel obtained in step S1) to obtain an assembly component;
[0045] S3) performing laser welding on the assembly components;
[0046] The copper-free medium-entropy alloy intermediate layer is made of the above-mentioned copper-free medium-entropy alloy interlayer.
[0047] In the welding process of titanium alloy and stainless steel, the present application first pre-treats the surfaces of titanium alloy and stainless steel, and the pre-treating specifically involves grinding the positions to be welded of titanium alloy and stainless steel clean. The titanium alloy is α titanium alloy, near α titanium alloy, α-β titanium alloy, β titanium alloy or commercially pure titanium alloy, wherein the titanium alloy may be TA1 or TC4; the stainless steel is austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, duplex stainless steel or precipitation hardening stainless steel, wherein the stainless steel may be 304 stainless steel or 316 stainless steel.
[0048] The present application places a copper-free medium-entropy alloy intermediate layer at a position to be welded between the titanium alloy and the stainless steel to obtain an assembly component, wherein the thickness of the copper-free medium-entropy alloy intermediate layer ranges from 0.5 mm to 1.5 mm.
[0049] When the assembly is laser welded in the present application, the laser power of the laser welding is 900-1100W, the speed is 15mm / s-20mm / s, the laser defocus is -25mm--15mm; the laser spot is offset 0.1mm-0.3mm to the stainless steel after aligning the middle of the copper-free medium entropy alloy intermediate layer. Preferably, the speed is 16mm / s, the laser defocus is -20mm; the laser spot is offset 0.2mm to the stainless steel after aligning the middle of the copper-free medium entropy alloy intermediate layer.
[0050] The technical solution of the present application is not limited to the specific implementation modes given below, but also includes any combination of the specific implementation modes.
[0051] Example 1
[0052] A method for welding titanium alloy and stainless steel in this embodiment comprises the following steps:
[0053] Step 1: weigh 32.6 g of Co particles, 32.46 g of Ni particles, and 28.18 g of V particles;
[0054] Step 2: Mix the components weighed in step 1 evenly and put them into a melting furnace, and evacuate the furnace (1×10 -3 MPa), then filled with argon, and intermittently smelted 6 times at a current of 200 A to achieve uniformity of composition and obtain an alloy ingot;
[0055] Step 3: Cut the obtained alloy ingot into 50mm×1mm×1mm by an electric spark cutting machine, and then remove the oil and oxide film on the surface of the alloy ingot by a polishing machine to make the surface of the alloy ingot have a metallic luster, so as to obtain a copper-free medium entropy alloy intermediate layer for laser welding of titanium alloy and stainless steel. Figure 1 As shown, Figure 1 The microstructure and element distribution of the prepared CoNiV, which is a single-phase FCC structure, has high strength and plasticity.
[0056] Step 4, pre-treat the surface of TC4 titanium alloy and 316L stainless steel, then place the copper-free medium entropy alloy intermediate layer between the titanium alloy and the stainless steel to be welded in a butt-jointed manner for clamping and pre-tightening (a ceramic pad can be used to prevent the copper-free medium entropy alloy intermediate layer from collapsing), obtain an assembly component, place the assembled assembly component in a protective cover, and introduce argon gas at a rate of 15L / min-20L / min for 1min to ensure that the weld will not be oxidized during the welding process, affecting the performance. Adjust the laser defocus to -20mm, the laser spot is aligned with the middle of the intermediate layer and deviates to 316L stainless steel by 0.2mm, the laser power is 1000W, the welding speed is 16mm / s, the cooling time is 30s, and the laser welding of TC4 titanium alloy and 316L stainless steel is completed to obtain a titanium alloy / stainless steel joint. It should be noted that the purity of the Co particles in this embodiment is 99.9%, the purity of the Ni particles is 99.9%, and the purity of the V particles is 99.9%.
[0057] The test shows that the tensile strength of the TC4 titanium alloy and 316L stainless steel joint can reach 331MPa. The TC4 titanium alloy and 316L stainless steel laser welded joint obtained in this embodiment was observed by electron microscope. Figure 2 and Figure 3 The following are electron microscope photos of the cross section of the laser welded joint obtained by using the copper-free medium entropy alloy intermediate layer for TC4 titanium alloy and 316L stainless steel, and the electron microscope photos of the microstructure of the TC4 side after welding. Due to the presence of Co, Ni and Fe elements in stainless steel, the main body of the weld presents a single-phase FCC structure after welding, with good plasticity, while a Ti-rich layer and a compound layer are generated on the titanium alloy side. Since the V element has a high solid solubility in Ti, it can greatly improve the performance of the compound at the reaction layer, alleviate the brittleness of the joint, and effectively improve the strength of the weld.
[0058] Example 2
[0059] A method for welding titanium alloy and stainless steel in this embodiment comprises the following steps:
[0060] Step 1: weigh 32.6 g of Co particles, 32.46 g of Ni particles, and 28.18 g of V particles;
[0061] Step 2: Mix the components weighed in step 1 evenly and put them into a melting furnace, and evacuate the furnace (1×10 -3 MPa), then filled with argon, and intermittently smelted 6 times at a current of 200 A to achieve uniformity of composition and obtain an alloy ingot;
[0062] Step 3, cutting the obtained alloy ingot into 50 mm × 1 mm × 1 mm by an electric spark cutting machine, and then removing the oil and oxide film on the surface of the alloy ingot by a polishing machine, so that the surface of the alloy ingot has a metallic luster, that is, obtaining a copper-free medium entropy alloy intermediate layer for laser welding of titanium alloy and stainless steel;
[0063] Step 4, pre-treat the surface of TC4 titanium alloy and 316L stainless steel, then place the copper-free medium entropy alloy intermediate layer between the titanium alloy and the stainless steel to be welded in a butt-jointed manner for clamping and pre-tightening (a ceramic pad can be used to prevent the copper-free medium entropy alloy intermediate layer from collapsing), obtain an assembly component, place the assembled assembly component in a protective cover, and pass argon gas at a rate of 15L / min-20L / min for 1min to ensure that the weld will not be oxidized during the welding process, affecting the performance. Adjust the laser defocus to -20mm, the laser spot is aligned with the middle of the intermediate layer and deviates to 316L stainless steel by 0.2mm, the laser power is 900W, the welding speed is 16mm / s, the cooling time is 30s, and the laser welding of TC4 titanium alloy and 316L stainless steel is completed to obtain a titanium alloy / stainless steel joint. It should be noted that the purity of the Co particles in this embodiment is 99.9%, the purity of the Ni particles is 99.9%, and the purity of the V particles is 99.9%.
[0064] According to tests, the tensile strength of TC4 titanium alloy and 316L stainless steel joints can reach 235MPa.
[0065] Example 3
[0066] A method for welding titanium alloy and stainless steel in this embodiment comprises the following steps:
[0067] Step 1: weigh 32.6 g of Co particles, 32.46 g of Ni particles, and 28.18 g of V particles;
[0068] Step 2: Mix the components weighed in step 1 evenly and put them into a melting furnace, and evacuate the furnace (1×10 -3 MPa), then filled with argon, and intermittently smelted 6 times at a current of 200 A to achieve uniformity of composition and obtain an alloy ingot;
[0069] Step 3, cutting the obtained alloy ingot into 50 mm × 1 mm × 1 mm by an electric spark cutting machine, and then removing the oil and oxide film on the surface of the alloy ingot by a polishing machine, so that the surface of the alloy ingot has a metallic luster, that is, obtaining a copper-free medium entropy alloy intermediate layer for laser welding of titanium alloy and stainless steel;
[0070] Step 4, pre-treat the surface of TC4 titanium alloy and 316L stainless steel, then place the copper-free medium entropy alloy intermediate layer between the titanium alloy and the stainless steel to be welded in a butt-jointed manner for clamping and pre-tightening (a ceramic pad can be used to prevent the copper-free medium entropy alloy intermediate layer from collapsing), obtain an assembly component, place the assembled assembly component in a protective cover, and introduce argon gas at a rate of 15L / min-20L / min for 1min to ensure that the weld will not be oxidized during the welding process, affecting the performance. Adjust the laser defocus to -20mm, the laser spot is aligned with the middle of the intermediate layer and deviates to 316L stainless steel by 0.2mm, the laser power is 800W, the welding speed is 16mm / s, the cooling time is 30s, and the laser welding of TC4 titanium alloy and 316L stainless steel is completed to obtain a titanium alloy / stainless steel joint. It should be noted that the purity of the Co particles in this embodiment is 99.9%, the purity of the Ni particles is 99.9%, and the purity of the V particles is 99.9%.
[0071] According to tests, the tensile strength of TC4 titanium alloy and 316L stainless steel joints can reach 158MPa.
[0072] Example 4
[0073] A method for welding titanium alloy and stainless steel in this embodiment comprises the following steps:
[0074] Step 1: weigh 32.6 g of Co particles, 32.46 g of Ni particles, and 28.18 g of V particles;
[0075] Step 2: Mix the components weighed in step 1 evenly and put them into a melting furnace, and evacuate the furnace (1×10 -3 MPa), then filled with argon, and intermittently smelted 6 times at a current of 200 A to achieve uniformity of composition and obtain an alloy ingot;
[0076] Step 3, cutting the obtained alloy ingot into 50 mm × 1 mm × 1 mm by an electric spark cutting machine, and then removing the oil and oxide film on the surface of the alloy ingot by a polishing machine, so that the surface of the alloy ingot has a metallic luster, that is, obtaining a copper-free medium entropy alloy intermediate layer for laser welding of titanium alloy and stainless steel;
[0077] Step 4, pre-treat the surface of TC4 titanium alloy and 316L stainless steel, then place the copper-free medium entropy alloy intermediate layer between the titanium alloy and the stainless steel to be welded in a butt-jointed manner for clamping and pre-tightening (a ceramic pad can be used to prevent the copper-free medium entropy alloy intermediate layer from collapsing), obtain an assembly component, place the assembled assembly component in a protective cover, and introduce argon gas at a rate of 15L / min-20L / min for 1min to ensure that the weld will not be oxidized during the welding process, affecting the performance. Adjust the laser defocus to -20mm, the laser spot is aligned with the middle of the intermediate layer and deviates to 316L stainless steel by 0.2mm, the laser power is 1100W, the welding speed is 16mm / s, the cooling time is 30s, and the laser welding of TC4 titanium alloy and 316L stainless steel is completed to obtain a titanium alloy / stainless steel joint. It should be noted that the purity of the Co particles in this embodiment is 99.9%, the purity of the Ni particles is 99.9%, and the purity of the V particles is 99.9%.
[0078] According to tests, the tensile strength of TC4 titanium alloy and 316L stainless steel joints can reach 265MPa.
[0079] Example 5
[0080] A method for welding titanium alloy and stainless steel in this embodiment comprises the following steps:
[0081] Step 1: weigh 32.6 g of Co particles, 32.46 g of Ni particles, and 28.18 g of V particles;
[0082] Step 2: Mix the components weighed in step 1 evenly and put them into a melting furnace, and evacuate the furnace (1×10 -3 MPa), then filled with argon, and intermittently smelted 6 times at a current of 200 A to achieve uniformity of composition and obtain an alloy ingot;
[0083] Step 3, cutting the obtained alloy ingot into 50 mm × 1 mm × 1 mm by an electric spark cutting machine, and then removing the oil and oxide film on the surface of the alloy ingot by a polishing machine, so that the surface of the alloy ingot has a metallic luster, that is, obtaining a copper-free medium entropy alloy intermediate layer for laser welding of titanium alloy and stainless steel;
[0084] Step 4, pre-treat the surface of TC4 titanium alloy and 316L stainless steel, then place the copper-free medium entropy alloy intermediate layer between the titanium alloy and the stainless steel to be welded in a butt-jointed manner for clamping and pre-tightening (a ceramic pad can be used to prevent the copper-free medium entropy alloy intermediate layer from collapsing), obtain an assembly component, place the assembled assembly component in a protective cover, and introduce argon gas at a rate of 15L / min-20L / min for 1min to ensure that the weld will not be oxidized during the welding process, affecting the performance. Adjust the laser defocus to -20mm, the laser spot is aligned with the middle of the intermediate layer and deviates to 316L stainless steel by 0.2mm, the laser power is 1200W, the welding speed is 16mm / s, the cooling time is 30s, and the laser welding of TC4 titanium alloy and 316L stainless steel is completed to obtain a titanium alloy / stainless steel joint. It should be noted that the purity of the Co particles in this embodiment is 99.9%, the purity of the Ni particles is 99.9%, and the purity of the V particles is 99.9%.
[0085] According to tests, the tensile strength of TC4 titanium alloy and 316L stainless steel joints can reach 171MPa.
[0086] Comparative Example 1
[0087] The welding method of titanium alloy and stainless steel in Comparative Example 1 is substantially the same as that in Example 1, except that: Comparative Example 1 uses FeCoCrNiCu high entropy alloy as an intermediate layer to achieve laser welding of TC4 titanium alloy and 304 stainless steel.
[0088] After testing, the tensile strength of the TC4 titanium alloy and 316L stainless steel joint is 161MPa, which is lower than the tensile strength of the copper-free medium entropy alloy intermediate layer used in the present invention. It can be understood that the comparison between the above tensile strengths is mainly the comparison between the highest tensile strengths of the comparative example and the embodiment, that is, the tensile strength of the TC4 titanium alloy and 304 stainless steel joints in the comparative example 1, and the tensile strength of the TC4 titanium alloy and 316L stainless steel joints in the embodiment 1. The main body of the weld after laser welding is FCC+Cu(s, s), and the titanium alloy interface is mainly composed of various proportions of intermetallic compounds formed by Ti and elements such as Fe, Co, Ni, and Cr. By adding a small amount of Cu element, the titanium alloy interface region segregates a Cu-based solid solution, which relieves the stress at the interface. However, the compound formed by Ti and elements such as Fe, Co, Ni, and Cr in the reaction zone still has a large hardness, which is higher than the parent material and the main body of the weld on both sides, which causes the brittleness of the joint. It is still difficult to avoid this problem by adjusting the Cu element content.
[0089] Comparative Example 2
[0090] The metallurgical systems of the titanium alloy and stainless steel in Comparative Example 2 and Example 1 are partially similar, except that: Comparative Example 2 uses a multi-component Ti-based medium-entropy alloy brazing material, which includes a Ti-Mn-Fe-Ni-Co-V-Cr seven-component medium-entropy alloy brazing material and a Ti-Mn-Fe-Ni-Co-V six-component medium-entropy alloy brazing material, which is used for vacuum brazing of TiAl alloys to obtain brazed joints with higher strength.
[0091] The brazed joint obtained in Comparative Example 2 is not the same as the welded joint obtained in Example 1. The reasons are as follows: First, the welding method is different. The welding method used in Comparative Example 2 is brazing, while the welding method used in Example 1 is laser welding. Second, the application materials are different. The copper-free medium entropy alloy intermediate layer of Example 1 focuses on achieving high-strength bonding between titanium alloy and stainless steel; while the multi-Ti-based medium entropy alloy brazing material is mainly used for the connection of the same metals such as TiAl, Ti-Al-Nb, etc.; if the multi-Ti-based medium entropy alloy brazing material is used for the connection of titanium alloy and stainless steel dissimilar metals, the elements such as Ti, Mn, Fe, Cr, etc. will produce a large amount of brittle phases, deteriorating the joint performance, but the elements such as Ti, Mn, Fe, Cr, etc. in the multi-Ti-based medium entropy alloy brazing material are indispensable for the connection of the same metals such as TiAl, Ti-Al-Nb, etc.; Third, there are great differences in the connection methods. The design idea of the six-element and seven-element brazing materials in Comparative Example 2 is to reduce the melting point through different eutectic components. These elements can be adjusted within a certain proportion, but cannot be deleted. For the laser welding in Example 1, it is not necessary to lower the melting point, but the extra elements make the compound system complicated, which is not conducive to welding. In addition, if a multi-element Ti-based medium entropy alloy brazing material is used to laser weld titanium alloy and stainless steel, the brittleness of the joint will be seriously increased. Ti and Fe will react with each other in the molten pool to form brittle compounds such as TiFe and Ti2Fe. The high mixing enthalpy of the Cr element and its Cr-based solid solution and other Cr-rich phases will precipitate during solidification. These phases often have high hardness, are inconsistent with the matrix, and are prone to cracking.
[0092] In summary, the copper-free medium-entropy alloy intermediate layer of the present application can well realize the laser welding connection between titanium alloy and stainless steel. The main body of the weld is FCC solid solution structure, the structure transition on the titanium alloy side is uniform, and the compound brittleness is low, which makes the joint have good comprehensive performance. The high-entropy interlayer manufacturing process is simple, easy to operate, and easy to promote.
[0093] It is obvious to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present application.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and are not limiting. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A copper-free medium-entropy alloy interlayer, characterized in that: Composed of Co, Ni and V, in percentage by mass, including: Co: 34% to 40%, Ni: 34% to 40%, V: 20% to 32%.
2. The copper-free medium-entropy alloy interlayer according to claim 1, characterized in that: The copper-free medium-entropy alloy interlayer comprises: Co: 34.96% to 39.31%, Ni: 34.82% to 38.75%, and V: 22.94% to 30.22%.
3. The copper-free medium-entropy alloy interlayer according to claim 1, characterized in that: The method for preparing the copper-free medium-entropy alloy interlayer comprises the following steps: A) preparing ingredients according to the mass percentage of the copper-free medium-entropy alloy interlayer, and then smelting to obtain an alloy ingot; B) preparing the alloy ingot into copper-free medium-entropy alloy interlayers in different usage forms.
4. The copper-free medium-entropy alloy interlayer according to claim 1 or 3, characterized in that: The copper-free medium-entropy alloy interlayer can be used in one or more of the following forms: smelting alloy block, smelting alloy crushed particles, smelting alloy flakes, smelting alloy powder, rapidly cooled foil strips and powder sintered bodies.
5. Use of the copper-free medium-entropy alloy interlayer according to any one of claims 1 to 4 in laser welding of titanium alloy and stainless steel.
6. A method for welding titanium alloy and stainless steel, comprising the following steps: S1) pretreating the surfaces of the titanium alloy and the stainless steel; S2) placing a copper-free medium entropy alloy intermediate layer at a position to be welded between the titanium alloy and the stainless steel obtained in step S1) to obtain an assembly component; S3) performing laser welding on the assembly components; The copper-free medium-entropy alloy intermediate layer is made of the copper-free medium-entropy alloy interlayer according to any one of claims 1 to 4.
7. The welding method according to claim 6, characterized in that: The thickness of the copper-free medium entropy alloy intermediate layer in the assembly component ranges from 0.5 mm to 1.5 mm.
8. The welding method according to claim 6, characterized in that: The titanium alloy is α titanium alloy, near-α titanium alloy, α-β titanium alloy, β titanium alloy or commercially pure titanium alloy, and the stainless steel is austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, duplex stainless steel or precipitation hardening stainless steel.
9. The welding method according to claim 6, characterized in that: The laser power of the laser welding is 900-1100W, the speed is 15mm / s-20mm / s, and the laser defocusing amount is -25mm--15mm.
10. The welding method according to claim 9, characterized in that: During laser welding, the laser spot is aligned with the center of the copper-free medium entropy alloy intermediate layer and then deviates toward the stainless steel by 0.1mm to 0.3mm.